EFFICIENCY OF THE ENTERPRISE, AND FACTORS AFFECTING IT - E. Knyazeva; E. Shapoval (Вестник университета)
The article explores the issues of understanding the efficiency of the enterprise, considers the effectiveness in terms of targeted, rational or economical use of resources. The conceptual apparatus of efficiency, discovered by leading scientists in terms of the possibility of solving a problem or achieving a goal in the most rational variant, is explored. Conceptually, the notion of efficiency from the point of view of an effective method or the possibility of solving a problem was determined. The understanding of the influence of factors on the efficiency of enterprises’ activity is presented. The factors inherent in the category of effectiveness, assigned to the group of external and internal, are determined.